Olive pomace oil can improve blood lipid profile: a randomized, blind, crossover, controlled clinical trial in healthy and at-risk volunteers - González-Rámila, Susana; Sarriá, Beatriz; Seguido, Miguel A.; García-Cordero, Joaquín; Mateos, Raquel; Bravo, Laura (European journal of nutrition, 2023)
Purpose This study aimed to assess the effect of dietary consumption of olive pomace oil (OPO) on blood lipids (primary outcome) and other cardiovascular disease (CVD) risk factors (blood pressure, inflammation and endothelial function as secondary outcomes). Methods A randomized, controlled, blind, crossover intervention was carried out in healthy and at-risk (hypercholesterolemic) subjects. Participants consumed daily 45 g of OPO or high-oleic acid sunflower oil (HOSO) as control oil during 4 weeks. Results OPO significantly reduced low-density lipoprotein cholesterol (LDL-C; P = 0.003) and apolipoprotein B (Apo B; P = 0.022) serum concentrations, and LDL/HDL ratio ( P = 0.027) in healthy and at-risk volunteers. These effects were not observed with HOSO. Blood pressure, peripheral artery tonometry (PAT), endothelial function and inflammation biomarkers were not affected. Conclusions Regular consumption of OPO in the diet could have hypolipidemic actions in subjects at cardiovascular risk as well as in healthy consumers, contributing to CVD prevention. Clinical trial registry NCT04997122, August 8, 2021, retrospectively registered.